The Effect of Leaflead Education on Pregnant Women's Compliance in Consuming Blood Influence Tablets at Pujon Batu Public Health Center - Novy Angelina Christyolivia; Sulistiyah Sulistiyah (Lembaga Pengembangan Kinerja Dosen, 2025)
Iron deficiency anemia is a significant public health problem in pregnant women, because it can cause maternal and fetal complications. Compliance with iron tablet consumption is often low due to limited knowledge, side effects, and cultural misconceptions. Leaflet-based education is a low-cost intervention that has the potential to improve understanding and compliance. This study aims to analyze the effect of leaflet education on the adherence of iron tablet consumption in pregnant women at the Pujon Health Center, Batu. The research design used a quasi-experiment with a pretest-posttest control group design. A total of 40 pregnant women were divided into an intervention group (n = 20) that received leaflet education and a control group (n = 20) that received standard counseling. Compliance was measured over four weeks through self-consumption records and tablet count calculations, while knowledge was assessed with a structured questionnaire. Data analysis used the Chi-square test with a significance level of p < 0.05. Results showed a significant improvement in adherence in the intervention group, with 70% of pregnant women complying compared to 15% in the control group (p = 0.001). Leaflet education also increased knowledge scores and consistency of iron tablet consumption. The conclusion of this study confirms that leaflet education is effective in increasing iron supplementation adherence, so it is recommended to be integrated into routine antenatal services to prevent anemia and support maternal and fetal health.